Optimizing Edge Gaming Slices through an Enhanced User Plane Function and Analytics in Beyond-5G Networks - Silva, Bruno Marques da; Rodrigues Moreira, Larissa Ferreira; de Oliveira Silva, Flávio; Moreira, Rodrigo (Anais do Workshop de Pesquisa Experimental da Internet do Futuro (WPEIF); 2025: Anais do XVI Workshop de Pesquisa Experimental da Internet do Futuro, 2025)
The latest generation of games and pervasive communication technologies poses challenges in service management and Service-Level Agreement compliance for mobile users. State-of-the-art edge-gaming techniques enhance throughput, reduce latency, and leverage cloud computing. However, further development of core functions such as the User Plane Function (UPF) is needed for non-intrusive user latency measurement. This paper proposes a closed-loop architecture integrating the Network Data Analytics Function (NWDAF) and UPF to estimate user latency and enhance the 5G control plane by making it latency-aware. The results show that embedding an artificial intelligence model within NWDAF enables game classification and opens new avenues for mobile edge gaming research.